Burn patient care lost in good manufacturing practices? - Dimitropoulos, G. (Ann Burns Fire Disasters, 2016)
Application of cell therapies in burn care started in the early 80s in specialized hospital centers world-wide. Since 2007, cell therapies have been considered as “Advanced Therapy Medicinal Products” (ATMP), so classified by European Directives along with associated Regulations by the European Parliament. Consequently, regulatory changes have transformed the standard linear clinical care pathway into a more complex one. It is important to ensure the safety of cellular therapies used for burn patients and to standardize as much as possible the cell sources and products developed using cell culture procedures. However, we can definitely affirm that concentrating the bulk of energy and resources on the implementation of Good Manufacturing Practice (GMP) alone will have a major negative impact on the care of severely burned patients world-wide. Developing fully accredited infrastructures and training personnel (required by the new directives), along with obtaining approval for clinical trials to go ahead, can be a lengthy process.We discuss whether or not these patients could benefit from cell therapies provided by standard in-hospital laboratories, thus avoiding having to meet rigid regulations concerning the use of industrial pharmaceutical products. “Hospital Exemption” could be a preferred means to offer burn patients a customized and safe product, as many adaptations may be required throughout their treatment pathway. Patients who are in need of rapid treatment will be the ones to suffer the most from regulations intended to help them.